Isolation of Scutellarein from Pygmaeopremna Herbacea Roxb - Vinay Kumar Verma, N. U. Siddiqui, Mohd. Aslam (Journal of Applied Pharmaceutical Science)
From the ethyl acetate extract of the plant Pygmaeopremna herbacea Roxb. a tetrahydroxy flavone was isolated which on the basis of spectral studies was characterized as 5,6,7,4′- tetrahydroxy flavone (Scutellarein).